2011
DOI: 10.1007/s10329-011-0237-7
|View full text |Cite
|
Sign up to set email alerts
|

The positional behavior of pygmy marmosets (Cebuella pygmaea) in northwestern Bolivia

Abstract: Pygmy marmosets are distinctive given their diminutive body size, their year-round reliance upon exudates, and their use of morphologically adapted tegulae to engage in a high degree of claw-clinging behaviors associated with exudate exploitation. This project examined the positional behavior and habitat preferences of one group of pygmy marmosets in a secondary forest within the Department of Pando, northwestern Bolivia. Results from this study indicate that pygmy marmosets primarily use claw-clinging during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This was attributed to requirements for exudativory but, again, no values are given for the proportion of exudates in the different species' diets, supporting only observations in Garber et al (, ) that the presence of tegulae in callitrichids is linked to vertical foraging behavior. The advantages of claws and claw‐like nails in vertical substrate foraging were suggested to be of particular importance for smaller‐bodied species that regularly utilize vertical, large‐diameter surfaces, where they facilitate extra grip to compensate for limbs which have too short a reach to allow an effective contact angle to be subtended (Soligo and Martin, ; Jackson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to requirements for exudativory but, again, no values are given for the proportion of exudates in the different species' diets, supporting only observations in Garber et al (, ) that the presence of tegulae in callitrichids is linked to vertical foraging behavior. The advantages of claws and claw‐like nails in vertical substrate foraging were suggested to be of particular importance for smaller‐bodied species that regularly utilize vertical, large‐diameter surfaces, where they facilitate extra grip to compensate for limbs which have too short a reach to allow an effective contact angle to be subtended (Soligo and Martin, ; Jackson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Though originally considered a primitive character, it is now assumed that callitrichid tegulae are a derived specialization which facilitate the gum‐feeding behavior prevalent in marmosets and tamarins (Garber and Sussman, ; Sussman and Kinzey, ; Hamrick, ; Soligo and Müller, ). Garber et al () identified two major problems with this inference: first, although the presence of “claws” may be expected to aid vertical clinging, the postural behavior most commonly associated with gum‐feeding (Garber, , ; Jackson, ), the link between gum‐feeding and the presence of clawed digits, has not been demonstrated across species with differing degrees of exudativory; second, despite the considerable variability in the extent to which callitrichids exploit gums, all possess tegulae. Garber et al () agree with Cartmill () that the presence of tegulae is an adaptation which simply allows the family to exploit large‐diameter vertical supports.…”
mentioning
confidence: 99%
“…Pygmy marmoset populations have been shown to be severely affected by live capture, noise pollution, and habitat destruction (Torre, Yépez, & Snowdon, 2009). They are gum specialists, morphologically and behaviorally adapted for exudate feeding, but also eat fruit and insects (Jackson, 2011;Soini, 1982;Yépez, de la Torre, & Snowdon, 2005). They live in small, cooperatively breeding groups: a breeding female, her offspring from up to four successive litters, her mate and one or two additional adults (Soini, 1982).…”
Section: Study Speciesmentioning
confidence: 99%
“…This ability has resulted in changes to parts of the brain devoted to hand use and visual‐manual behaviors (Padberg et al, ). Marmosets have multiple adaptations, including a decreased body size, the reintroduction of claws versus nails on the digits for vertical climbing, and reduced eye movement capabilities with accompanied head cocking (Kaplan & Rogers, ; Jackson, ). Squirrel monkeys also engage in head cocking (Rumbaugh, 1968), and have a small ocular motor range and interocular distance which affect head movements during visual search (McCrea & Gdowski, ).…”
Section: Introductionmentioning
confidence: 99%